Moving forward on the left - Meehan, Eileen R. (Javnost (Ljubljana), 2004)
With the Soviet Union's demise, some academicians argued that Marxist scholarship was similarly irrelevant. Yet, critical voices are still raised in the United States and critical analyses of corporate America remain central in the political economy of mass communication. Within US communication research, 'political economist' is closely identified with the North American Critical School and thus with Marxist scholarship. While that glosses over the wide variety of positions taken by American practitioners of political economy, it is a fairly reasonable assumption within the field of communications. In the 1950s, a self-consciously critical approach emerged in the work of Dallas Smythe and Herbert I. Schiller. Although ostracized by the field's administrative 'mainstream', Smythe and Schiller published widely, found an organizational home in the International Association for Media and Communication Research, and inspired a generation of scholars. Their legacy remains vibrant as critical communications research has taken root in the academy, figured in the creation of anti-neo-conservative movements, founded and sustained professional organizations, played a major role in the critique of the mainstream, developed traditions of internal debate and critique, and been targeted for scholarly attack. While much remains to be done, the critical school is clearly moving forward.
Keywords: United States of America; ZDA; democracy; demokracija; mass media; množični mediji; komuniciranje; communication; sociologija komunikacij